Influence of ammonium nitrate incorporation on the thermal decomposition kinetics of nitrostarch-based energetic composite - Nassima Sahnoun; Amir Abdelaziz; Djalal Trache; Ahmed Fouzi Tarchoun; Hani Boukeciat; Amel Meslem; Weiqiang Pang (FirePhysChem, 2025)
The primary objective of this study was the development of a novel energetic composite formulation, focusing on the elucidation of the influence of incorporating an energetic oxidizer, ammonium nitrate (AN), on the thermal decomposition behavior of a double-base composition, comprising nitrated potato starch (NPS) or nitrostarch as the polymeric binder and diethylene glycol dinitrate (DEGDN) as an energetic plasticizer. The optimal composition of the energetic composite was determined through theoretical performance calculations using the CEA-NASA program. The optimized AN@NPS-DEGDN energetic composite was comprehensively characterized using Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and scanning electron microscopy (SEM). The FTIR results demonstrated that the NPS-DEGDN demonstrated good chemical compatibility with AN. The textural analysis by SEM revealed that the AN particles are homogeneously dispersed within the NPS-DEGDN matrix. Thermal analysis results showed that the introduction of AN significantly enhanced the thermolysis-released heat of the double-base formulation. Furthermore, isoconversional kinetic modeling exhibited a substantial decrease in the composite thermolysis activation energy, corroborating the excellent catalytic effect of AN on the NPS-DEGDN composite. These findings highlight the potential of the developed AN@NPS-DEGDN composite as a promising candidate for advanced energetic applications, offering improved performance and environmental sustainability.